2012
DOI: 10.1158/0008-5472.can-12-0337
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Therapeutic Responses in Melanoma by Inhibition of IRAK-1,-4

Abstract: Toll-like receptors (TLR) are expressed by a variety of cancers, including melanoma, but their functional contributions in cancer cells are uncertain. To approach this question, we evaluated the effects of stimulating or inhibiting the TLR/IL-1 receptor-associated kinases IRAK-1 and IRAK-4 in melanoma cells where their functions are largely unexplored. TLRs and TLR-related proteins were variably expressed in melanoma cell lines, with 42% expressing activated phospho-IRAK-1 constitutively and 85% expressing hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 24 publications
2
57
0
Order By: Relevance
“…We next investigated the phosphorylation status of IRAK4 (p-IRAK4) in 103 resected human PDAC samples by immunohistochemistry using a phospho-antibody that was previously reported in melanoma(27). We found p-IRAK4 to be present and significantly stronger in the ductal epithelia of 20 out of 30 (or 66.7%) PDAC samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next investigated the phosphorylation status of IRAK4 (p-IRAK4) in 103 resected human PDAC samples by immunohistochemistry using a phospho-antibody that was previously reported in melanoma(27). We found p-IRAK4 to be present and significantly stronger in the ductal epithelia of 20 out of 30 (or 66.7%) PDAC samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from PDAC, targeting the IRAK1/4 cascade has been shown to be a promising strategy in other malignancies including DLBCL(29, 40), myelodysplastic syndrome(41), T-cell ALL(42), melanoma(27), breast cancer(43), and head and neck cancer(44), further underscoring the urgent need to develop potent IRAK inhibitors for clinical testing. Another study showed that TAK1 inhibition could augment the effect of chemotherapy in PDAC(45).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that the IRAK1/4 inhibitor is effective in the treatment of melanoma [60] as well as myelodysplastic syndrome [61]. Since the IRAK family plays a key role in NF-κB signaling, IRAK2 may also be a therapeutic target for NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma cells can express functional TLRs (17, 29). The Human Protein Atlas, an online immunohistochemistry (IHC) database evaluating the expression of various proteins and cancer types, shows TLR5 to be expressed at low levels on 30% of patients with melanoma.…”
Section: Resultsmentioning
confidence: 99%